2021
DOI: 10.1038/s41421-021-00326-6
|View full text |Cite|
|
Sign up to set email alerts
|

SIRT2-mediated deacetylation and deubiquitination of C/EBPβ prevents ethanol-induced liver injury

Abstract: Protein acetylation has emerged to play pivotal roles in alcoholic liver disease (ALD). Sirutin 2 (SIRT2) is a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase involved in the regulation of aging, metabolism, and stress. However, the role of SIRT2 in ALD remains unclear. Here, we report that the SIRT2-mediated deacetylation–deubiquitination switch of CCAAT/enhancer-binding protein beta (C/EBPβ) prevents ALD. Our results showed that hepatic SIRT2 protein expression was negatively correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…G-protein mediated event genes were enriched for pAUDIT, which includes signal transduction at the synapse, and is consistent with the WNT6-PRKCG interaction noted above (and possible immune function). Gene interactions within the deubiquitination REACTOME pathway were associated with pAUDIT, suggesting the importance of post-translational modification in alcohol use as has been hypothesized 67 , and highlighting the need for additional 'omics integration into such analyses. Notably, three of the coexpression network modules identified by Gandal et al 30,64 were associated with BMI or pAUDIT.…”
Section: Functional and Pathway Interaction Enrichmentmentioning
confidence: 81%
“…G-protein mediated event genes were enriched for pAUDIT, which includes signal transduction at the synapse, and is consistent with the WNT6-PRKCG interaction noted above (and possible immune function). Gene interactions within the deubiquitination REACTOME pathway were associated with pAUDIT, suggesting the importance of post-translational modification in alcohol use as has been hypothesized 67 , and highlighting the need for additional 'omics integration into such analyses. Notably, three of the coexpression network modules identified by Gandal et al 30,64 were associated with BMI or pAUDIT.…”
Section: Functional and Pathway Interaction Enrichmentmentioning
confidence: 81%
“…It is reported that p38MAPK mediates the stress signal to induce senescence 41 . Previous studies have reported that several genes that regulate aging are involved in the development of ALD, such as SIRT1, SIRT2 and SIRT6 42 - 44 . Importantly, CREG1 is also involved in the ageing process 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of SIRT2 was found in HFD-fed rats compared with rats fed a normal diet [ 96 , 97 ]. The present study revealed that SIRT1 and claudin-1 expressions showed opposite trends in the HFD-fed rat kidneys.…”
Section: Discussionmentioning
confidence: 99%